If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (-6.2x + 6)(-4) = 0 Reorder the terms: (6 + -6.2x)(-4) = 0 Reorder the terms for easier multiplication: -4(6 + -6.2x) = 0 (6 * -4 + -6.2x * -4) = 0 (-24 + 24.8x) = 0 Solving -24 + 24.8x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '24' to each side of the equation. -24 + 24 + 24.8x = 0 + 24 Combine like terms: -24 + 24 = 0 0 + 24.8x = 0 + 24 24.8x = 0 + 24 Combine like terms: 0 + 24 = 24 24.8x = 24 Divide each side by '24.8'. x = 0.9677419355 Simplifying x = 0.9677419355
| 26.5=3+5.5 | | 6a-3=2+7a | | k-(-5)=-5 | | 5+3(q-4)=2(q+3) | | (u-4)-(3u^2-5u-4)= | | y=5.5+3x | | 3x+3=2x-12 | | 7-5y=4-4y | | (-4.3x+2)(-6)= | | x+7x-2x=9b+2x | | 7x-5+7=6x-6 | | -3=2+a/11 | | y=3x+5.5 | | 8(x-3)=-(x-12) | | n+5=5-4n | | 5x-9y=-1 | | (3-2i)(6+7i)= | | -5d*10d-7d+8= | | 9(x+1)=6-2(9x+7) | | 12x-(2x-9)=79 | | 13x-290=0 | | 15x^2=-11x+14 | | 8C^2+18C-35=0 | | (X^2)=2x+99 | | 2(x-2)+10(x+2)+(3x-8)=180 | | 5y-3+6(2y-4)=-4(2y-3)+9 | | 15=2x-50 | | 62-8x=12+2x | | 2727=h+(-8) | | 10-3x=-20 | | 4x^2-9x+130=0 | | 80-4y=160 |